Political and social context of not attaining the Millennium Development Goal to reduce poverty - Marco Palma-Solís; Diana Gil-González; Carlos Álvarez-Dardet; María Teresa Ruiz-Cantero (The World Health Organization, 2008)
OBJECTIVE: Eradication of poverty is Target 1 of the first of eight Millennium Development Goals, which were adopted by world leaders at the United Nations General Assembly in the year 2000. This study aims to explore the influence of political and social context in the achievement of poverty eradication. METHODS: A retrospective ecological study was carried out to explore associations between progress towards the achievement of Target 1 in 2002 and political and social context variables. The study contained cross-sectional estimates in 1990, 1995, 2000 and 2002. The analysis and observation unit was the countries (n = 88). A descriptive analysis was made, as well as simple and multiple analyses with logistic regression. FINDINGS: Of the 88 countries studied, 71 (80.7%) are not on track to achieving the target of eradicating poverty. The factor most associated with non-attainment of this goal was reduced government consumption per capita (odds ratio, OR: 13.8; 95% confidence interval, CI: 2.92-65.26). In the multiple regression analysis, the most significant factors are: reduced government consumption per capita (OR: 9.8; 95% CI: 1.82-52.75), losses in the balance between imports and exports (OR: 5.3; 95% CI: 1.32-21.54) and more inequality in family income (OR: 4.7; 95% CI: 1.12-20.01). CONCLUSION: Progress towards achievement of Target 1 seems to be hindered, fundamentally, by the significant reduction in government consumption in certain countries and the absence of redistribution policies. To understand the political determinants of poverty, more attention must be paid to the national and international political milieu, which seem to have a relevant impact on this problem and hence on population health.